What Does a Tourist See, or, an Environmental – Aesthetic Evaluation of a Street View in Szeged (Hungary) - Hornyák, Sándor; Karancsi, Zoltán; Korom, Annamária; Győri, Ferenc (Turizam, 2023)
Nowadays, it is in our fast-developing big cities, that the steps taken to improve the inhabitants’ physical and mental health conditions have become increasingly important. The aim of health improvement can also be facilitated by extending the proportion of well-cared-for green areas in city centres, or, by rehabilitating particular buildings, streets or districts; these developments have an obviously beneficial psychological effect on people. The establishment of such ’livable cities’ can be rewarding from the point view of tourism, too, because, in general, tourists are happy if they can spend their free time in an urban environment which is devoid of visual conflicts. This is the reason why our team of researchers attempted to identify a so-called ’Visual Livability Index’ (VLI) with the aim of qualifying the state our urban environment is in. When identifying the formerly mentioned index, primarily those positive and negative characteristic features are determined, which may have an impact on the aesthetic value of the settlement. Then, after summarizing the results of evaluations, the next step taken is when the streets, squares, whole districts of the given settlement, or even the entire city is qualified with the help of the VLI index, thus making the results comparable with those of other similar settlements.